2020
DOI: 10.1200/jco.2020.38.15_suppl.e13600
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of adenoid cystic carcinoma in the United States.

Abstract: e13600 Background: Adenoid cystic carcinoma (ACC) is a rare malignancy of the secretory glands, accounting for approximately 1% of head and neck cancers and 10% of salivary gland neoplasms. ACC primarily occurs in the major and minor salivary glands; however, it is found in other sites of the head and neck, breast, female genital tract, prostate and skin. There is limited scientific literature on the epidemiology of ACC and no published incidence or prevalence estimates across all anatomic sites. Methods: Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The average age of patients in this study aligns with previous reports, indicating that ACC commonly affects individuals in their late forties [35][36][37][38][39][40][41]. The extended time span between symptom onset and diagnosis observed in this study aligns with most case series, although it differs from a few reports [35,42,43]. This discrepancy could be attributed to the slow-growing nature of ACC and its manifestation through nonspecific signs.…”
Section: Discussionsupporting
confidence: 85%
“…The average age of patients in this study aligns with previous reports, indicating that ACC commonly affects individuals in their late forties [35][36][37][38][39][40][41]. The extended time span between symptom onset and diagnosis observed in this study aligns with most case series, although it differs from a few reports [35,42,43]. This discrepancy could be attributed to the slow-growing nature of ACC and its manifestation through nonspecific signs.…”
Section: Discussionsupporting
confidence: 85%
“…However, some small-sample and unicentric studies have reported a male-to-female ratio of 1.6 : 1 [ 3 ]. The neoplasm can affect any age group, but it predominantly manifests between the 6th and 7th decades of life which has estimated that there are between 1,450 and 1,660 new SACC cases per year in the USA [ 2 , 4 ]. However, the incidence of the disease showed a significant decline between 1973 and 2007 [ 2 ], which could be attributed to the early recognition resulting from the advances in the diagnostic and treatment provisions.…”
Section: Resultsmentioning
confidence: 99%